Estudo químico e avaliação do potencial moluscicida da espécie vegetal serjania glabrata kunth (sapindaceae) - Grzesiuk, Viviane Leticia (2008)
The present works was aimed at the chemical study and evaluation of molluscicidal potential of the vegetable specie Serjania glabrata Kunth, which belongs to the family Sapindaceae. This family is characterized by the accumulation of quebrachitol and triterpenic saponins (often toxic) in their parenchymatous tissues, and their seeds an unusual class of composts, the cyanolipids. The plant was separated into leaves, twigs and seeds and subjected to different methods of extraction and purification. The fractionation of hexane extract from the leaves in different solvents using chromatography techniques resulted in the isolation of two mixtures of unsaturated hydrocarbons and triterpene ß-amyrin. The amino acid N-methyl-trans-4-hydroxyl-Lproline was isolated from the ethanolic extract of branches after fractionation in column chromatography. With the hexane extract of the seeds was isolated a cyanolipid type I, the 1-cyano-2-hydroymethylprop-2-en-1-ol-diester. It was also employed the methodology of precipitation saponins and subsequent dialysis of the precipitate of the ethanolic extract of the seeds. Through the column chromatography fractionation was isolated the substance quebrachitol. The evaluation of the molluscicidal potential indicated the hexane extracts of branches as active and hexane extract of the seeds as very active, with the LC50 value of 137,6 µg.mL-1 and 28,3 µg.mL-1, respectively.